High performance in sewing: guaranteeing seam quality through control of sewing dynamics - Carvalho, Miguel (2007)
To maintain an acceptable level of competitiveness of the apparel industry in developed countries with the open market after 2004, manufacturers should be able to answer to reduced quantities, short delivery dates and an increasing number of styles in production and an increasing level of quality specifications. In this environment machine set-up acquires a great relevance. Therefore, the development of intelligent sewing machines in order to reduce the human intervention during adjustment situations, detection of operation anomalies and solemnity capacity adjusts for its amend, guaranteeing high quality levels, has an increasing importance. The dynamics of the seam have been the main studied aspects, through the study of the tensions and consumption of the sewing threads during the formation of the stitch.